Relationship between Marketing Capability and Marketing Survival: An Empirical Study of Fashion Retailing Thailand - Pornpakdee, Supannee; Inthasang, Chatchai (Ph.D. in Social Sciences Journal, 2026)
The objective of this study is to examine the level of opinions for fashion retail entrepreneurs on marketing capability, marketing advantage, and marketing survival. Examine the relationship of marketing capability affects marketing advantage that leading to the marketing survival of fashion retailing in Thailand. A questionnaire was used to collect data from 322 entrepreneurs or managers in the fashion retailing. The validity and reliability were checked, which are content validity by an expert, the result of discriminant validity tested by factor analysis shows a value between 0.811 - 0.920, and the result of Cronbach’s Alpha Coefficient test of reliability value between 0.877 - 0.921. This research analyzes the data using the descriptive statistics method and multiple regressions for hypotheses testing. The results revealed that the entrepreneurs or managers had the overall opinion on the marketing capability, marketing advantage, and marketing survival of fashion retailing, Thailand in the highest level. In addition, the results of hypothesis testing found that marketing capability (marketing learning, customer relationship management, and marketing adaptation) have a significant and positive effect on marketing advantage. Likewise, marketing advantage explicitly leads to the marketing survival of fashion retailing, Thailand